Application of peer teaching learning method to improve learning motivation, learning results and student retention on the material of the digestion system - Fitri Raudhah (Jurnal Edubio Tropika, 2018)
This study aims to determine the application of peer teaching model to improve learning motivation, learning outcomes and student retention on digestive system material in MAS DarulUlum Banda Aceh. The data were collected in January 2017. The method used in this research is the experimental method with the pretest post control design design. This research was conducted in two classes namely XI MIA 1 as control class and XI MIA 2 as experiment class. The instrument used was a motivational questionnaire to see students' learning motivation, an objective test consisting of 20 multiple choice questions to see the learning outcomes, an objective test consisting of 20 multiple poses that had been randomized to see student retention. Data analysis using Mann Whitney U test with SPSS 17.0 for windows at significant level 0,05. The result of the average value of learning motivation of experimental class is 76,47 and control class is 72,18. At the value of N-gain the experimental class is 0.72 and the control class is 0.65. At the mean retention grade theexperimental class is 17.49 and the control class is 16.8. Of the three variables that have been measured it shows that the application of peer teaching method can improve learning motivation, learning outcomes andstudent retention on digestive system material in MAS DarulUlum Banda Aceh.Keywords: Peer Teaching, Learning Motivation, Learning Outcomes, Student Retention and Digestive System.